Recent advances in type 1 diabetes. Issue 7 (5th October 2015) - Kyi, Mervyn; Wentworth, John M; Nankervis, Alison J; Fourlanos, Spiros; Colman, Peter G
Summary: Type 1 diabetes (T1D) is caused by an autoimmune attack on pancreatic beta cells that leads to insulin deficiency. The incidence of T1D in Australia has doubled over the past 20 years. T1D treatment focuses on physiological insulin replacement, aiming for near‐normal blood glucose levels. Hypoglycaemia is a significant cause of morbidity and mortality in T1D. Optimal T1D management is complex, and is enhanced by empowering individuals in all aspects of managing diabetes. New technologies, including insulin pumps, continuous glucose monitors and sensor‐augmented pumps, can assist people achieve better glycaemic control and reduce the risk of severe hypoglycaemia. Women with T1D can achieve significantly better outcomes during pregnancy and for their infants by planning for their pregnancy and by intensive glycaemic control. Several trials are underway that seek to identify the determinants of autoimmunity and to develop therapies that prevent T1D in at‐risk individuals. Pancreatic and islet cell transplants are proven therapies, but are only offered to individuals with diabetes and renal failure (pancreas) or severe hypoglycaemia unawareness (islet cell transplants). Although T1D is still associated with considerable premature mortality, recent findings show that a significant improvement in life expectancy has occurred.